Insect-induced effects on plants and possible effectors used by galling and leaf-mining insects to manipulate their host-plant. (January 2016) - Giron, David; Huguet, Elisabeth; Stone, Graham N.; Body, Mélanie
Graphical abstract: Highlights: Insect galls are among the most emblematic examples of plant manipulations. Leaf-miners may have evolved similar strategies to face similar lifestyle constraints. Characterization of insect salivary effectors can help identifying targeted plant functions. Abstract: Gall-inducing insects are iconic examples in the manipulation and reprogramming of plant development, inducing spectacular morphological and physiological changes of host-plant tissues within which the insect feeds and grows. Despite decades of research, effectors involved in gall induction and basic mechanisms of gall formation remain unknown. Recent research suggests that some aspects of the plant manipulation shown by gall-inducers may be shared with other insect herbivorous life histories. Here, we illustrate similarities and contrasts by reviewing current knowledge of metabolic and morphological effects induced on plants by gall-inducing and leaf-mining insects, and ask whether leaf-miners can also be considered to be plant reprogrammers. We review key plant functions targeted by various plant reprogrammers, including plant-manipulating insects and nematodes, and functionally characterize insect herbivore-derived effectors to provide a broader understanding of possible mechanisms used in host-plant manipulation. Consequences of plant reprogramming in terms of ecology, coevolution and diversification of plant-manipulating insects are also discussed.